Composite tungsten oxide microparticle dispersion and composite tungsten oxide microparticle dispersion liquid

JP7631668B2Active Publication Date: 2025-02-19SUMITOMO METAL MINING CO LTD
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
JP2020052583
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2019-11-08
Filing Date
2020-03-24
Publication Date
2025-02-19
Estimated Expiration
2040-03-24

AI Technical Summary

Benefits of technology

【0014】 本発明に係る複合タングステン酸化物微粒子分散体および複合タングステン酸化物微粒子分散液は、優れた赤外線吸収特性および耐候性を有しながら青味が除去されており、意匠性に優れている。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007631668000002
    Figure 0007631668000002
  • Figure 0007631668000003
    Figure 0007631668000003
  • Figure 0007631668000001
    Figure 0007631668000001
Patent Text Reader

Abstract

To provide a composite tungsten oxide fine particle dispersion that ensures excellent infrared absorption properties and weather resistance and yet suppresses a blue taste to such an extent that b* value becomes a positive value, and a composite tungsten oxide fine particle dispersion liquid.SOLUTION: A composite tungsten oxide fine particle dispersion contains composite tungsten oxide fine particles with crystallite diameters of 25 nm or more and 85 nm or less and a solid medium.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a composite tungsten oxide microparticle dispersion and a composite tungsten oxide microparticle dispersion liquid which have a good visible light transmittance, excellent infrared absorption properties, and a predetermined color. [Background technology]

[0002] In recent years, the demand for infrared absorbers has been rapidly increasing, and many patent applications related to infrared absorbers have been filed. Looking at these applications from a functional perspective, for example, some applications are aimed at suppressing an increase in temperature inside a room while maintaining brightness by blocking infrared light while sufficiently taking in visible light in the field of window materials for various buildings and vehicles.

[0003] The present inventors disclosed an infrared-shielding material microparticle dispersion in which infrared-shielding material microparticles are dispersed in a medium, and the excellent optical properties, electrical conductivity, and production method of the infrared-shielding material microparticle dispersion in Patent Document 1. In particular, the infrared-shielding material microparticle dispersion had superior infrared-shielding properties to conventional shielding materials.

[0004] The above-mentioned infrared shielding material fine particles are fine particles of tungsten oxide represented by the general formula WyOz (wherein W is tungsten, O is oxygen, and 2.2≦z / y≦2.999), or / and fine particles of tungsten oxide represented by the general formula MxWyOz (wherein M is H, He, an alkali metal, an alkaline earth metal, a rare earth element, Mg, Zr, Cr, Mn, Fe, Ru, Co, Rh, Ir, Ni, Pd, Pt, Cu, Ag, Au, Zn, Cd, Al, Ga, I n, Tl, Si, Ge, Sn, Pb, Sb, B, F, P, S, Se, Br, Te, Ti, Nb, V, Mo, Ta, Re, Be, Hf, Os, Bi, I, W is tungsten, O is oxygen, 0.001≦x / y≦1, 2.2≦z / y≦3.0), and the infrared shielding material fine particles have a particle diameter of 1 nm or more and 800 nm or less.

[0005] Patent Document 2 proposes a laminated glass in which an ultraviolet-curable resin having composite tungsten oxide particles and / or hexaboride particles dispersed therein is filled between glass sheets, and which has excellent infrared absorbing properties, a low haze value, and excellent visible light transparency.

[0006] However, the infrared shielding material microparticle dispersions and laminated glass disclosed in Patent Documents 1 and 2 each have a bluish tinge due to the presence of a composite tungsten oxide, and therefore need to be improved from the standpoint of design.

[0007] Therefore, for example, Patent Document 3 has proposed a near-infrared shielding filter that contains the above-mentioned composite tungsten oxide and a compound having a maximum absorption in the wavelength region of 300 to 500 nm, thereby suppressing or eliminating the blue tint specific to the composite tungsten oxide. [Prior art documents] [Patent documents]

[0008] [Patent Document 1] JP 2010-168430 A [Patent Document 2] JP 2010-202495 A [Patent Document 3] Japanese Patent Application Publication No. 11-181336 [Patent Document 4] JP 2008-304798 A Summary of the Invention [Problem to be solved by the invention]

[0009] However, according to the studies of the present inventors, the near-infrared shielding filter disclosed in, for example, Patent Document 3, which is said to suppress or remove the blue tint, does not sufficiently suppress the blue tint. On the other hand, for example, in various filters having infrared absorbing properties disclosed in Patent Document 4, b* in the L*a*b* color system shows a negative value. However, the compound having a maximum absorption in the wavelength region of 300 to 500 nm used together with the composite tungsten oxide in the filter is an organic material, and therefore has low weather resistance and cannot withstand the usage environment in fields such as various buildings and vehicle window materials.

[0010] Here, the inventors have found that in composite tungsten oxide microparticles, the value of b* changes from negative to positive as the particle size of the microparticles increases.The inventors have attempted to solve the above problem by increasing the particle size of the composite tungsten oxide microparticles.However, they have found that the larger the particle size of the microparticles, the more the light scattering in the short wavelength region increases, and the visible light transmittance of the composite tungsten oxide microparticles decreases, making it impossible to ensure excellent infrared absorption properties.

[0011] The present invention has been made under the above circumstances, and the problem to be solved by the present invention is to provide a composite tungsten oxide microparticle dispersion and a composite tungsten oxide microparticle dispersion liquid in which the blue tinge is suppressed to such an extent that the b* value is a positive value while maintaining excellent infrared absorption characteristics and weather resistance. [Means for solving the problem]

[0012] In order to solve the above-mentioned problems, the present inventors have conducted research into the structure of removing the blueness of composite tungsten oxide microparticles while ensuring excellent infrared absorption properties and weather resistance.As a result, they have come up with the idea that the above-mentioned problems can be solved by making composite tungsten oxide microparticles with a crystallite diameter of 25nm or more and 85nm or less contained in composite tungsten oxide microparticle dispersion and composite tungsten microparticle dispersion liquid, and have completed the present invention.

[0013] That is, the first invention for solving the above-mentioned problems is: The composite tungsten oxide microparticle dispersion contains composite tungsten oxide microparticles having a crystallite size of 25 nm or more and 85 nm or less, and a solid medium. Effect of the Invention

[0014] The composite tungsten oxide microparticle dispersion and composite tungsten oxide microparticle dispersion liquid according to the present invention have excellent infrared absorption properties and weather resistance while being free of any bluish tinge, and are therefore excellent in design properties. [Brief description of the drawings]

[0015] [Figure 1] FIG. 2 is a schematic plan view of a crystal structure in composite tungsten oxide microparticles having hexagonal crystals. [Diagram 2] 1 shows a transmitted light profile of a composite tungsten oxide microparticle dispersion liquid. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0016] The embodiments for carrying out the present invention will be described in the following order: [1] composite tungsten oxide microparticles and a method for producing the same; [2] composite tungsten oxide microparticle dispersion liquid having a predetermined crystallite size and a method for producing the same; [3] composite tungsten oxide microparticle dispersion powder and a method for producing the same; and [4] composite tungsten oxide microparticle dispersion and a method for producing the same.

[0017] [1] Composite tungsten oxide particles and their manufacturing method In general, it is known that materials containing free electrons show a reflection / absorption response to electromagnetic waves around the range of sunlight with wavelengths of 200 nm to 2600 nm due to plasma oscillation. It is known that when powders of such substances are made into fine particles smaller than the wavelength of light, the geometric scattering of the visible light range (wavelengths of 380 nm to 780 nm) is reduced, and transparency in the visible light range is obtained. In this invention, the term "transparency" is used to mean "low scattering and high transmittance for light in the visible light range."

[0018] Generally, tungsten oxide (WO3) does not have effective free electrons, so it has little absorption and reflection characteristics in the infrared region and is not effective as an infrared absorbing particle. On the other hand, WO3 with oxygen deficiency and composite tungsten oxides in which electropositive elements such as Na are added to WO3 are known to be conductive materials with free electrons. Furthermore, analysis of single crystals of these materials with free electrons suggests the response of the free electrons to light in the infrared region.

[0019] The composite tungsten oxide microparticles (A) having a predetermined composition according to the present invention and a method for producing the same will be described below in the following order: (1) the composition of the composite tungsten oxide microparticles (A), (2) the crystal structure of the composite tungsten oxide microparticles (A), (3) the optical properties of the composite tungsten oxide microparticles (A), and (4) the method for producing the composite tungsten oxide microparticles (A).

[0020] (1) Composition of composite tungsten oxide particles (A) The inventors have found that within a specific portion of the composition range of tungsten and oxygen, there exists a range that is particularly effective as infrared absorbing microparticles, and have come up with the idea of ​​composite tungsten oxide microparticles that are transparent in the visible light region and absorb in the infrared region.

[0021] Furthermore, by adding the element M described below to the above-mentioned WO3 to form a composite tungsten oxide, free electrons are generated in the WO3, and strong absorption characteristics derived from the free electrons are expressed, particularly in the near-infrared region, making it effective as infrared absorbing microparticles with wavelengths around 1000 nm.

[0022] That is, more efficient composite tungsten oxide microparticles can be obtained by combining the control of the amount of oxygen and the addition of the element M that generates free electrons to the WO3. When the general formula of the composite tungsten oxide microparticles obtained by combining the control of the amount of oxygen and the addition of the element M that generates free electrons is written as MxWyOz (where M is the element M, W is tungsten, and O is oxygen), composite tungsten oxide microparticles that satisfy the relationships of 0.001≦x / y≦1 and 2.0≦z / y≦3 are desirable.

[0023] First, the value of x / y, which indicates the amount of element M added, will be described. If the value of x / y is greater than 0.001, a sufficient amount of free electrons is generated in the composite tungsten oxide, and the desired infrared absorption effect can be obtained. The more the amount of element M added, the greater the supply of free electrons and the higher the infrared absorption efficiency, but the effect saturates when the value of x / y is about 1. In addition, if the value of x / y is less than 1, it is preferable because it is possible to avoid the generation of an impurity phase in the composite tungsten oxide microparticles.

[0024] Furthermore, the element M is preferably one or more elements selected from H, He, alkali metals, alkaline earth metals, rare earth elements, Mg, Zr, Cr, Mn, Fe, Ru, Co, Rh, Ir, Ni, Pd, Pt, Cu, Ag, Au, Zn, Cd, Al, Ga, In, Tl, Si, Ge, Sn, Pb, Sb, B, F, P, S, Se, Br, Te, Ti, Nb, V, Mo, Ta, Re, Be, Hf, Os, Bi, I, and Yb.

[0025] Here, from the viewpoint of stability in the MxWyOz to which the element M is added, the element M is more preferably one or more elements selected from among alkali metals, alkaline earth metals, rare earth elements, Mg, Zr, Cr, Mn, Fe, Ru, Co, Rh, Ir, Ni, Pd, Pt, Cu, Ag, Au, Zn, Cd, Al, Ga, In, Tl, Si, Ge, Sn, Pb, Sb, B, F, P, S, Se, Br, Te, Ti, Nb, V, Mo, Ta, and Re. And, from the viewpoint of improving the optical properties and weather resistance of the infrared absorbing fine particles, the element M is even more preferably an alkaline earth metal element, a transition metal element, a Group 4B element, or a Group 5B element.

[0026] Regarding the value of z / y, which indicates the control of the amount of oxygen, when 2.0≦z / y≦3.0, there is a supply of free electrons due to the amount of the element M added. For this reason, 2.0≦z / y≦3.0 is preferable, 2.2≦z / y≦3.0 is more preferable, and 2.45≦z / y≦3.0 is even more preferable.

[0027] (2) Crystal structure of composite tungsten oxide particles (A) When the composite tungsten oxide fine particles (A) according to the present invention have a hexagonal crystal structure, the fine particles have improved transmission in the visible light region and improved absorption in the infrared region. This hexagonal crystal structure will be described with reference to FIG. 1, which is a schematic plan view.

[0028] In FIG. 1, six octahedra formed of WO6 units, indicated by the reference symbol 11, are assembled to form a hexagonal void, and an element M, indicated by the reference symbol 12, is arranged in the void to form one unit, and a large number of these units are assembled to form a hexagonal crystal structure. In order to obtain the effect of improving light transmission in the visible light region and improving light absorption in the infrared region, it is sufficient that the composite tungsten oxide microparticles contain the unit structure explained with reference to FIG. 1, and the composite tungsten oxide microparticles (A) may be crystalline or amorphous.

[0029] When the cations of element M are added to the hexagonal gaps, the transmission of light in the visible light region is improved, and the absorption of light in the infrared region is improved. Generally, the hexagonal crystal is easily formed when an element M with a large ionic radius is added. Specifically, the hexagonal crystal is easily formed when Cs, K, Rb, Tl, In, Ba, Li, Ca, Sr, Fe, or Sn is added. Of course, elements other than these may be used as long as the above-mentioned element M is present in the hexagonal gaps formed by the WO6 units, and the elements are not limited to the above-mentioned elements.

[0030] When the composite tungsten oxide fine particles (A) having a hexagonal crystal structure have a uniform crystal structure, the amount of the added element M is preferably 0.2 or more and 0.5 or less, more preferably 0.33, in terms of the value of x / y. When the value of x / y is 0.33, it is considered that the above-mentioned element M is arranged in all of the hexagonal voids.

[0031] In addition, tetragonal and cubic composite tungsten oxides other than hexagonal are also effective as infrared absorbing particles. The absorption position in the infrared region tends to change depending on the crystal structure, and the absorption position tends to move to the long wavelength side in the order of cubic crystal < tetragonal crystal < hexagonal crystal. In addition, the absorption in the visible light region is small in the order of hexagonal crystal, tetragonal crystal, and cubic crystal. Therefore, it is preferable to use hexagonal composite tungsten oxide for applications that transmit more visible light and absorb more infrared light. However, the tendency of the optical characteristics described here is only a rough tendency, and changes depending on the type and amount of added element and the amount of oxygen, and the present invention is not limited to this.

[0032] (3) Optical properties of composite tungsten oxide particles (A) The composite tungsten oxide fine particles (A) according to the present invention largely absorb light in the near infrared region, particularly in the vicinity of a wavelength of 1000 nm, and therefore the transmitted color tone is often bluish.

[0033] (4) Manufacturing method of composite tungsten oxide fine particles (A) The composite tungsten oxide fine particles (A) according to the present invention can be obtained by heat-treating a starting material, which is a tungsten compound, in a reducing gas atmosphere to obtain composite tungsten oxide fine particles, and setting the crystallite size of the fine particles to the predetermined value described above. Hereinafter, the composite tungsten oxide (A) according to the present invention will be described in the order of (i) starting material and (ii) heat treatment.

[0034] (i) Starting material The starting material of the composite tungsten oxide according to the present invention is a mixture containing tungsten and the element M, each in the form of a simple substance or a compound. As the tungsten raw material, it is preferably any one or more selected from tungsten acid powder, tungsten trioxide powder, tungsten dioxide powder, hydrated tungsten oxide powder, tungsten hexachloride powder, ammonium tungstate powder, or hydrated tungsten oxide powder obtained by dissolving tungsten hexachloride powder in alcohol and then drying, or hydrated tungsten oxide powder obtained by dissolving tungsten hexachloride in alcohol, adding water to precipitate it, and drying it, or tungsten compound powder obtained by drying an ammonium tungstate aqueous solution, and metallic tungsten powder. Examples of the raw material of the element M include, but are not limited to, the element M itself, chloride salts, nitrates, sulfates, oxalates, oxides, carbonates, tungstates, hydroxides of the element M.

[0035] Weigh the starting materials described above, and when the composite tungsten oxide according to the present invention is labeled as MxWyOz (where M is the M element, W is tungsten, and O is oxygen) using the general formula, mix them with a predetermined amount that satisfies 0.001 < x / y ≤ 1. At this time, it is preferable that the respective raw materials related to tungsten and the element M are as uniform as possible, and if possible, uniformly mixed at the molecular level. Therefore, it is most preferable that each of the above-mentioned starting materials is mixed in the form of a raw material solution. For this reason, it is preferable that each starting material is soluble in a solvent such as water or an organic solvent.

[0036] If each starting material is soluble in a solvent such as water or an organic solvent, the starting materials can be thoroughly mixed with the solvent, and then mixed together, and the solvent can be evaporated to produce a mixture of the starting materials for the tungsten compound according to the present invention. However, when a solvent capable of dissolving each of the starting materials cannot be prepared, the mixture of the starting materials for the tungsten compound can also be produced by thoroughly and uniformly mixing each of the starting materials using a known means such as a ball mill.

[0037] (ii) Heat treatment Next, the heat treatment in a reducing gas atmosphere will be described. The heat treatment temperature may be appropriately selected depending on the amount of starting materials to be subjected to the heat treatment, but for example, it is preferable to heat treat at 300°C or more and 900°C or less, and more preferably 500°C or more and 850°C or less. If it is 300°C or more, the reaction of forming the composite tungsten oxide having a hexagonal crystal structure according to the present invention progresses, and if it is 900°C or less, it is preferable because unintended by-products such as composite tungsten oxide fine particles having a structure other than hexagonal crystal structure and metallic tungsten are unlikely to be formed.

[0038] The reducing gas in this case is not particularly limited, but is preferably H2. When H2 is used as the reducing gas, the composition of the reducing atmosphere may be appropriately selected depending on the amount of the starting material to be subjected to the heat treatment, but it is preferable to mix H2 in an inert gas such as Ar or N2 at a volume percentage of 0.1% to 5.0%. If necessary, a heat treatment may be performed in an inert gas atmosphere after the reduction treatment in a reducing gas atmosphere. In this case, the heat treatment in the inert gas atmosphere is preferably performed at a temperature of 400° C. or higher and 1200° C. or lower.

[0039] [2] Composite tungsten oxide microparticle dispersion having a specified crystallite size and its manufacturing method A composite tungsten oxide microparticle dispersion liquid can be produced by dispersing composite tungsten oxide microparticles (A), i.e., infrared absorbing microparticles, in a liquid solvent. In the present invention, a composite tungsten oxide microparticle dispersion liquid (B) is produced in which composite tungsten oxide microparticles (A) having a crystallite size of 25 nm or more and 85 nm or less are dispersed in a predetermined solvent.

[0040] The composite tungsten oxide microparticle dispersion (B) having the predetermined crystallite size can be obtained by adding the composite tungsten oxide microparticles (A) and, if desired, an appropriate amount of a dispersant, a coupling agent, a surfactant, etc. to a liquid solvent, and carrying out a wet grinding and dispersion treatment under different conditions.

[0041] The composite tungsten oxide microparticle dispersion (B) having a predetermined crystallite size will be described below in the following order: (1) solvent, (2) dispersant, (3) crystallite size of the composite tungsten oxide microparticles (A), (4) dispersed particle size of the composite tungsten oxide microparticles (A), and (5) method for producing the composite tungsten oxide microparticles (A) having a predetermined crystallite size.

[0042] (1) Solvent The solvent for the composite tungsten oxide microparticle dispersion liquid is required to have the function of maintaining the dispersibility of the composite tungsten oxide microparticles and the function of preventing coating defects when the composite tungsten oxide microparticle dispersion liquid is applied.

[0043] As the solvent, water, an organic solvent, vegetable oil, a compound derived from vegetable oil, a petroleum-based solvent, oils and fats, a liquid resin, a liquid plasticizer for plastics, or a mixture thereof can be selected to produce a composite tungsten oxide microparticle dispersion. As the organic solvent that satisfies the above requirements, various organic solvents such as alcohols, ketones, hydrocarbons, glycols, and water can be selected.

[0044] Specific examples of the solvent include alcohol-based solvents such as methanol, ethanol, 1-propanol, isopropanol, butanol, pentanol, benzyl alcohol, and diacetone alcohol; ketone-based solvents such as acetone, methyl ethyl ketone, methyl propyl ketone, methyl isobutyl ketone, cyclohexanone, and isophorone; ester-based solvents such as 3-methyl-methoxy-propionate; glycol derivatives such as ethylene glycol monomethyl ether, ethylene glycol monoethyl ether, ethylene glycol isopropyl ether, propylene glycol monomethyl ether, propylene glycol monoethyl ether, propylene glycol methyl ether acetate, and propylene glycol ethyl ether acetate; amides such as formamide, N-methylformamide, dimethylformamide, dimethylacetamide, and N-methyl-2-pyrrolidone; aromatic hydrocarbons such as toluene and xylene; and halogenated hydrocarbons such as ethylene chloride and chlorobenzene. Among these, organic solvents with low polarity are preferred, and in particular, isopropyl alcohol, ethanol, 1-methoxy-2-propanol, dimethyl ketone, methyl ethyl ketone, methyl isobutyl ketone, toluene, propylene glycol monomethyl ether acetate, n-butyl acetate, etc. These solvents can be used alone or in combination of two or more.

[0045] Preferred vegetable oils include linseed oil, sunflower oil, tung oil, sesame oil, cottonseed oil, rapeseed oil, soybean oil, rice bran oil, olive oil, coconut oil, palm oil, and dehydrated castor oil.

[0046] As the compound derived from vegetable oil, fatty acid monoesters obtained by directly esterifying fatty acids of vegetable oil with monoalcohols, vegetable oil ethers, and the like are preferable.

[0047] As the petroleum-based solvent, Isopar E, Exxor Hexane, Exxor Heptane, Exxor E, Exxor D30, Exxor D40, Exxor D60, Exxor D80, Exxor D95, Exxor D110, Exxor D130 (all manufactured by Exxon Mobil Corporation), etc. are preferable.

[0048] As the liquid resin, methyl methacrylate and the like are preferable. As the liquid plasticizer for plastics, preferred examples include a plasticizer which is a compound of a monohydric alcohol and an organic acid ester, an ester-based plasticizer such as a polyhydric alcohol organic acid ester compound, and a phosphoric acid-based plasticizer such as an organic phosphoric acid-based plasticizer. Among them, triethylene glycol di-2-ethylhexanoate, triethylene glycol di-2-ethylbutyrate, and tetraethylene glycol di-2-ethylhexanoate are more preferable because of their low hydrolysis property.

[0049] (2) Dispersant The dispersant, coupling agent, and surfactant can be selected according to the application, but it is preferable that they have an amine-containing group, a hydroxyl group, a carboxyl group, or an epoxy group as a functional group. These functional groups are adsorbed to the surface of the composite tungsten oxide microparticles, prevent the composite tungsten oxide microparticles from agglomerating, and have the effect of uniformly dispersing the composite tungsten oxide microparticles according to the present invention even in the infrared absorbing film.

[0050] Suitable dispersants include, but are not limited to, phosphate ester compounds, polymeric dispersants, silane coupling agents, titanate coupling agents, aluminum coupling agents, etc. Polymeric dispersants include acrylic polymeric dispersants, urethane polymeric dispersants, acrylic block copolymer polymeric dispersants, polyether dispersants, polyester polymeric dispersants, etc.

[0051] The amount of the dispersant added is preferably in the range of 10 parts by mass to 1000 parts by mass, more preferably in the range of 20 parts by mass to 200 parts by mass, relative to 100 parts by mass of the composite tungsten oxide microparticles. If the amount of the dispersant added is in the above range, the composite tungsten oxide microparticles will not aggregate in the dispersion liquid, and dispersion stability will be maintained.

[0052] (3) Crystallite size of composite tungsten oxide particles (A) In order to obtain composite tungsten oxide particles (A) according to the present invention that have excellent infrared absorption properties while suppressing blueness to such an extent that the b* value is a positive value, it is essential that the crystallite size is 25 nm or more and 85 nm or less, preferably 30 nm or more and 50 nm or less.

[0053] The crystallite size of the composite tungsten oxide fine particles (A) according to the present invention is measured by measuring the X-ray diffraction pattern by powder X-ray diffraction method (θ-2θ method) and by analysis by the Rietveld method. The crystallite size can be determined by Rietveld analysis based on the analysis results of XRD (X-ray diffraction method). Specifically, the crystallite size can be determined by performing Rietveld analysis based on the diffraction peak position of the composite tungsten oxide fine particles that appears at a diffraction angle 2θ = 10 ° to 120 ° with a Cu source using a powder X-ray diffractometer "X'Pert-PRO / MPD" manufactured by PANalytical, Spectris Co., Ltd.

[0054] (4) Dispersion particle size of composite tungsten oxide particles (A) Since the dispersed particle diameter of the composite tungsten oxide microparticles according to the present invention, which will be described later, is selected depending on the intended use, the dispersed particle diameter of the composite tungsten oxide microparticles (A) dispersed in the dispersion liquid (B) can be selected.

[0055] First, when used in applications where transparency must be maintained, it is preferable that the dispersed particles have a particle size of 800 nm or less. This is because particles smaller than 800 nm do not completely block light due to scattering, and can maintain visibility in the visible light range while efficiently maintaining transparency at the same time. In particular, when transparency in the visible light range is important, it is preferable to further consider scattering by particles.

[0056] When the reduction of scattering by the particles is important, the dispersion particle diameter is 200 nm or less, preferably 150 nm or less. The reason for this is that if the dispersion particle diameter of the particles is small, the scattering of light in the visible light region of wavelength 400 to 780 nm due to geometric scattering or Mie scattering is reduced, and the infrared absorbing film becomes like cloudy glass, and it is possible to avoid not being able to obtain clear transparency. That is, when the dispersion particle diameter is 200 nm or less, the geometric scattering or Mie scattering is reduced, and the Rayleigh scattering region is reached. In the Rayleigh scattering region, the scattered light is reduced in proportion to the sixth power of the particle diameter, so that the scattering is reduced and the transparency is improved as the dispersion particle diameter decreases. Furthermore, if the dispersed particle size is 150 nm or less, scattered light is extremely reduced, which is preferable. From the viewpoint of avoiding light scattering, it is preferable that the dispersed particle size is small, and if the dispersed particle size is 1 nm or more, industrial production is easy.

[0057] By setting the dispersed particle diameter to 800 nm or less, the haze value of the composite tungsten oxide microparticle dispersion liquid (B) or composite tungsten oxide microparticle dispersion (B) according to the present invention can be set to 30% or less with a visible light transmittance of 85% or less. If the haze value is more than 30%, it becomes like cloudy glass and clear transparency cannot be obtained. The dispersed particle size of the composite tungsten oxide fine particles (A) can be measured using an instrument based on the dynamic light scattering method, such as ELS-8000 manufactured by Otsuka Electronics Co., Ltd.

[0058] (5) Method for producing composite tungsten oxide microparticles (A) having a predetermined crystallite size The composite tungsten oxide microparticle dispersion liquid according to the present invention can be obtained by adding the composite tungsten oxide microparticles (A), a dispersant, and, if desired, a coupling agent, a surfactant, etc. to a liquid solvent and carrying out a wet grinding and dispersion treatment. In this case, by controlling the conditions of the wet grinding and dispersion treatment, it is possible to produce a composite tungsten oxide microparticle dispersion liquid (B) according to the present invention in which composite tungsten oxide microparticles (A) having a predetermined crystallite size are dispersed in a liquid solvent.

[0059] The method of wet grinding and dispersion treatment can be selected from among known methods as long as it is a method that can uniformly disperse the composite tungsten oxide microparticles in a solvent, and for example, methods such as bead milling, ball milling, sand milling, and ultrasonic dispersion can be used. In order to obtain a uniform composite tungsten oxide microparticle dispersion (B), various additives or dispersants may be added, or the pH may be adjusted.

[0060] The specific conditions for wet-milling and dispersion treatment depend on the specifications of the wet-milling device, the type of dispersant and solvent, etc. Therefore, a specific wet-milling device, dispersant and solvent are determined, a composite tungsten oxide microparticle dispersion is prototyped, and wet-milling and dispersion treatment conditions are found and set that will yield composite tungsten oxide microparticles (A) with a crystallite size of 25 nm or more and 85 nm or less.

[0061] [3] Composite tungsten oxide fine particle dispersion powder and its manufacturing method By removing the solvent from the composite tungsten oxide microparticle dispersion liquid (B) according to the present invention described above, a composite tungsten oxide microparticle dispersion powder (C) can be obtained. In order to remove the solvent from the composite tungsten oxide microparticle dispersion liquid (B), it is preferable to dry the composite tungsten oxide microparticle dispersion liquid (B) under reduced pressure. Specifically, the composite tungsten oxide microparticle dispersion liquid (B) is dried under reduced pressure while stirring, and the composite tungsten oxide microparticle-containing composition and the solvent component are separated. The pressure during the reduced pressure in the drying step is appropriately selected. The use of the reduced pressure drying method improves the efficiency of removing the solvent from the composite tungsten oxide microparticle dispersion liquid (B), and the mixed composite tungsten oxide microparticle powder of the present invention is not exposed to high temperatures for a long period of time, so that the mixed composite tungsten oxide microparticles dispersed in the microparticles do not aggregate, which is preferable. Furthermore, the productivity of the mixed composite tungsten oxide microparticles is increased, and the evaporated solvent can be easily recovered, which is also preferable from an environmental perspective.

[0062] [4] Composite tungsten oxide microparticle dispersion and its manufacturing method By dispersing the composite tungsten oxide microparticle dispersion liquid (B) or the composite tungsten oxide microparticle dispersion powder (C) according to the present invention in a solid medium, a composite tungsten oxide microparticle dispersion (D) such as a dispersion powder, a master batch, an infrared absorbing film, or an infrared absorbing plastic molded product can be produced.

[0063] As an example of a general use method, a method for producing an infrared absorbing film using the composite tungsten oxide microparticle dispersion (B) of the present invention will be described. The composite tungsten oxide microparticle dispersion (B) described above is mixed with a plastic or a monomer to prepare a coating liquid, and a coating film is formed on a substrate by a known method, whereby an infrared absorbing film can be produced. The infrared absorbing film is an example of the composite tungsten oxide microparticle dispersion (D) of the present invention.

[0064] The medium of the coating film can be selected according to the purpose, for example, from UV-curable resins, thermosetting resins, electron beam-curable resins, room temperature-curable resins, and thermoplastic resins. Specific examples include polyethylene resins, polyvinyl chloride resins, polyvinylidene chloride resins, polyvinyl alcohol resins, polystyrene resins, polypropylene resins, ethylene-vinyl acetate copolymers, polyester resins, polyethylene terephthalate resins, fluororesins, polycarbonate resins, acrylic resins, and polyvinyl butyral resins. These resins may be used alone or in combination. In addition, a binder using a metal alkoxide can be used. Representative examples of the metal alkoxides include alkoxides of Si, Ti, Al, Zr, and the like. The binders using these metal alkoxides can form oxide films by hydrolysis and condensation polymerization by heating, etc.

[0065] The substrate may be a film as described above, or may be a board if desired, and the shape is not limited. Transparent substrate materials include PET, acrylic, urethane, polycarbonate, polyethylene, ethylene-vinyl acetate copolymer, vinyl chloride, fluororesin, etc., which can be used depending on various purposes. In addition to resin, glass can be used.

[0066] Furthermore, the composite tungsten oxide microparticle dispersion (D) according to the present invention does not contain any organic material having poor weather resistance, and therefore has high weather resistance and can withstand the usage environments in fields such as window materials for various buildings and vehicles. EXAMPLES

[0067] The present invention will now be described in detail with reference to examples. However, the present invention is not limited to the following examples.

[0068] The crystallite size of the composite tungsten oxide nanoparticles was calculated by analyzing the X-ray diffraction pattern by the Rietveld method. The X-ray diffraction pattern was measured by the powder X-ray diffraction method (θ-2θ method) using a powder X-ray diffractometer (X'Pert-PRO / MPD manufactured by PANalytical, Spectris Co., Ltd.). The optical properties of the dispersion liquid consisting of at least one type of composite tungsten oxide microparticles and the dispersion consisting of at least one type of composite tungsten oxide microparticles were measured as a transmitted light profile at intervals of 5 nm in the wavelength range of 200 to 2600 nm using a spectrophotometer (U-4100 manufactured by Hitachi, Ltd.), and the visible light transmittance and solar transmittance were calculated according to JIS R 3106. The L*a*b* color system (D65 light source / 10-degree visual field) based on JIS Z 8701 was used as the color system, and the b* value was measured.

[0069] [Example 1] Hexagonal cesium tungsten bronze (Cs) with Cs / W (molar ratio) = 0.33 0.33 A mixed solution was obtained by mixing 8 mass% of tungsten oxide powder (registered trademark YM-01 manufactured by Sumitomo Metal Mining Co., Ltd.), 24 mass% of a polyacrylate-based dispersant, and 68 mass% of toluene as a solvent. 200 g of the obtained mixed solution was loaded into a paint shaker (manufactured by Asada Iron Works Co., Ltd.) together with 750 g of 0.3 mmφ ZrO2 beads, and subjected to a pulverization and dispersion treatment for 7 hours, thereby obtaining a composite tungsten oxide microparticle dispersion solution according to Example 1.

[0070] The composite tungsten oxide microparticle dispersion liquid according to Example 1 was diluted with toluene as a solvent so that the visible light transmittance was 80%. Then, the transmitted light profile was measured using a glass cell for measuring a spectrophotometer (manufactured by GL Sciences Inc., model number: S-10-SQ-1, material: synthetic quartz, optical path length: 1 mm). Before the measurement, the baseline of the transmitted light profile was measured in a state where the glass cell was filled with toluene as a solvent for the dispersion liquid. By measuring the baseline, the contributions of light reflection from the surface of the glass cell for the spectrophotometer and light absorption by the solvent can be canceled, and only the light absorption by the composite tungsten oxide nanoparticles is reflected in the transmitted light profile. From the obtained transmitted light profile, the visible light transmittance, solar radiation transmittance, and b* of the composite tungsten oxide microparticle dispersion liquid according to Example 1 were calculated. The evaluation results are shown in Table 1.

[0071] Next, the solvent was evaporated from the composite tungsten oxide microparticle dispersion liquid according to Example 1 by vacuum fluidized drying to obtain a composite tungsten oxide microparticle dispersion powder according to Example 1. The vacuum fluidized drying was performed using a vacuum crusher (24P manufactured by Ishikawa Factory Co., Ltd.). The rotation speed was 45 rpm / min, and the heater temperature was set to 70°C. The crystallite size of the composite tungsten oxide microparticles according to Example 1 contained in the obtained composite tungsten oxide microparticle dispersion powder according to Example 1 was measured and found to be 48 nm.

[0072] The composite tungsten oxide microparticle dispersion powder according to Example 1 and polycarbonate resin were dry-blended so that the infrared absorbing sheet, which is the composite tungsten oxide microparticle dispersion according to Example 1 obtained later, would have a visible light transmittance of about 80% (in this example, the composite tungsten oxide microparticles were blended so that the concentration was 0.045 mass%.) The resulting blend was kneaded at 290°C using a twin-screw extruder, extruded from a T-die, and formed into a sheet material with a thickness of 0.75 mm by a calendar roll method, thereby obtaining an infrared absorbing sheet, which is the composite tungsten oxide microparticle dispersion according to Example 1.

[0073] The transmitted light profile of the obtained infrared absorbing sheet was measured. From the transmitted light profile obtained, the visible light transmittance, solar radiation transmittance, and b* of the composite tungsten oxide microparticle dispersion according to Example 1 were calculated. The evaluation results are shown in Table 1. The transmitted light profile of the composite tungsten oxide microparticle dispersion according to Example 1 is shown by a solid line in FIG. 2.

[0074] [Example 2] A composite tungsten oxide microparticle dispersion liquid according to Example 2 was obtained by carrying out the same operations as in Example 1, except that the processing time of the wet grinding and dispersion treatment was changed to 13 hours as explained in Example 1. The solvent was removed from the obtained dispersion liquid, and the crystallite diameter of the composite tungsten oxide microparticles according to Example 2 contained in the obtained composite tungsten oxide microparticle dispersion powder according to Example 2 was measured and found to be 32 nm.

[0075] Except for using the composite tungsten oxide microparticle dispersion liquid of Example 2 instead of the composite tungsten oxide microparticle dispersion liquid of Example 1, the same operation as in Example 1 was carried out to obtain the composite tungsten oxide microparticle dispersion liquid of Example 2 and the composite tungsten oxide microparticle dispersion powder of Example 2, and the same evaluation as in Example 1 was carried out. The evaluation results are shown in Table 1. Moreover, the transmitted light profile of the composite tungsten oxide microparticle dispersion liquid of Example 2 is shown by the long dashed line in FIG. 2.

[0076] [Comparative Example 1] A composite tungsten oxide microparticle dispersion liquid according to Comparative Example 1 was obtained by carrying out the same operations as in Example 1, except that the processing time of the wet grinding and dispersion treatment was changed to 2 hours as explained in Example 1. The solvent was removed from the obtained dispersion liquid, and the crystallite diameter of the composite tungsten oxide microparticles according to Comparative Example 1 contained in the obtained composite tungsten oxide microparticle dispersion powder according to Comparative Example 1 was measured and found to be 88 nm.

[0077] Except for using the composite tungsten oxide microparticle dispersion liquid of Comparative Example 1 instead of the composite tungsten oxide microparticle dispersion liquid of Example 1, the composite tungsten oxide microparticle dispersion liquid of Comparative Example 1 and the composite tungsten oxide microparticle dispersion powder of Comparative Example 1 were obtained by the same operation as in Example 1, and evaluations were performed in the same manner as in Example 1. The evaluation results are shown in Table 1.

[0078] [Comparative Example 2] A composite tungsten oxide microparticle dispersion liquid according to Comparative Example 2 was obtained by carrying out the same operations as in Example 1, except that the processing time of the wet grinding and dispersion treatment was changed to 30 hours as explained in Example 1. The solvent was removed from the obtained dispersion liquid, and the crystallite diameter of the composite tungsten oxide microparticles according to Comparative Example 2 contained in the obtained composite tungsten oxide microparticle dispersion powder according to Comparative Example 2 was measured and found to be 22 nm.

[0079] Except for using the composite tungsten oxide microparticle dispersion liquid of Comparative Example 2 instead of the composite tungsten oxide microparticle dispersion liquid of Example 1, the composite tungsten oxide microparticle dispersion liquid of Comparative Example 2 and the composite tungsten oxide microparticle dispersion powder of Comparative Example 2 were obtained by performing the same operations as in Example 1, and the same evaluations were performed as in Example 1. The evaluation results are shown in Table 1. The transmitted light profile of the composite tungsten oxide microparticle dispersion liquid of Comparative Example 2 is shown by the short dashed line in FIG. 2.

[0080] [Table 1]

[0081] [summary] As is clear from Table 1, the composite tungsten oxide microparticle dispersion according to Example 1 or 2 (measured only with the composite tungsten microparticle component) and the composite tungsten oxide microparticle dispersion according to Example 1 both had a solar transmittance of 45% or less when the visible light transmittance was 80%, and a b* of 0 or more. This result demonstrated that the optical properties were excellent and the bluish tinge was suppressed. Furthermore, it was confirmed that the composite tungsten oxide microparticle dispersions according to Examples 1 and 2 have clearly lower solar radiation transmittance when the visible light transmittance is 80% and have excellent infrared absorption properties, compared to the composite tungsten oxide microparticle dispersion according to Comparative Example 1. On the other hand, the composite tungsten oxide microparticle dispersion according to Comparative Example 2 has a b* value of less than 0. Moreover, from the graph in FIG. 2, it was found that the composite tungsten oxide microparticle dispersion liquid according to Example 1 or 2 had a profile with a peak shifted to the long wavelength side compared to the composite tungsten oxide microparticle dispersion liquid according to Comparative Example 2.

Claims

1. The present invention includes Cs0.33WOz (2.0≦z≦3.0) fine particles having a crystallite diameter of 32 nm or more and 48 nm or less, and a polycarbonate resin as a solid medium, A composite tungsten oxide microparticle dispersion, characterized in that the solar radiation transmittance is 45% or less when the visible light transmittance is 80%, and the b* value is 0 or more when evaluated according to the L*a*b* color system (D65 light source / 10-degree visual field) based on JIS Z 8701.

2. A method for producing a toluene dispersion containing a polyacrylate-based dispersant, comprising dispersing Cs0.33WOz (2.0≦z≦3.0) fine particles having a crystallite diameter of 32 nm or more and 48 nm or less; A composite tungsten oxide microparticle dispersion liquid, characterized in that the solar radiation transmittance is 45% or less when the visible light transmittance is 80%, and the b* value is 0 or more when evaluated using the L*a*b* color system (D65 light source / 10-degree visual field) based on JIS Z 8701.

Citation Information

Patent Citations

  • Coating fluid for permselective membrane, permselective membrane, and multi layered permselective membrane

    JP1999181336A

  • Near-infrared shielding filter, optical filter for display, and display and plasma display panel using the filter

    JP2008304798A

  • Method for producing dispersion of composite tungsten oxide fine particle and method for producing molding using the dispersion and molding

    JP2010168430A

  • Heat ray shielding laminated glass and production method of the same

    JP2010202495A

  • Adhesive layer, near-infrared absorption film, laminated structure, laminate, adhesive composition, and method for producing same

    WO2018235833A1